The Psychology of Beauty - Howes, Ethel Puffer, 1872-1950 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Psychology of Beauty" by Ethel Puffer Howes is a scientific publication written in the early 20th century. The book explores the nature of beauty, aiming to blend philosophical theories and empirical psychological studies to provide a coherent understanding of aesthetic experience and its emotional impact on individuals. The opening of the work serves as a preface where Howes introduces the fundamental questions regarding the experience of beauty in both nature and art. She discusses the historical evolution of thought surrounding beauty, from speculative philosophical theories to empirical studies investigating the aesthetic experience. Howes emphasizes the need for an integrated approach that combines modern psychology with philosophy, proposing that understanding beauty requires a synthesis of various theories and facts about human perception and emotional response. The section sets the stage for a deeper exploration of beauty, its elements, and the psychological conditions that bring about aesthetic pleasure. (This is an automatically generated summary.)
Criticism and aesthetics -- The nature of beauty -- The aesthetic repose -- The beauty of fine art; The beauty of visual form; Space composition among the old masters -- The beauty of music -- The beauty of literature -- The nature of the emotions of the drama -- The beauty of ideas.
Release date is 2003-02-01
Keywords: Aesthetics